Concomitant novel ALK-SSH2, EML4-ALK and ARID2-ALK, EML4-ALK double-fusion variants and confer sensitivity to crizotinib in two lung adenocarcinoma patients, respectively - Hong Tao; Zhe Liu; Jing Mu; Fei Gai; Zhan Huang; Liang Shi (BMC, 2022)
Abstract Introduction Anaplastic lymphoma kinase (ALK) gene rearrangements, have been identified in approximately 2-7% of patients with lung adenocarcinoma (LUAD). However, co-occurrence of double ALK fusions in one patient was rare. Herein, we reported two Chinese female LUAD patients with confirmed double ALK fusion variants by next generation sequencing. Case presentation Case 1, a 38-year-old female was diagnosed as peripheral LUAD in left upper lobe with synchronous multiple intrapulmonary metastases (pT2N0M1b, stage IVa). And case 2, a 58-year-old female had left lower lobe primary LUAD and synchronous multiple lung metastases (pT4N2M1b, stage IVa). In both patients, tumor cells displayed strong expression of ALK protein. Genetic profiling by next generation sequencing showed both patients concurrently harbored two types of ALK rearrangements. Case 1 had an unreported ALK-SSH2/EML4-ALK double fusions, and case 2 had an another novel ARID2-ALK/EML4‐ALK double fusions. Both of these patients responded to ALK inhibitor crizotinib. Conclusions Our study reported two novel ALK fusion partners never reported, which expands the knowledge of ALK fusion spectrum and provides insight into therapeutic options for patients with double ALK fusions.